Forensic Basics of Modern Biometric Technologies - Sh. N. Khaziev (Теория и практика судебной экспертизы)
Forensic identification and modern biometric technologies have a common basis and have been closely developing together in various ways. Today new biometric technologies have emerged that utilize previously inaccessible properties and characteristics of humans. The article examines how forensic identification principles are applied in the creation of such new technologies.Promising areas of collaboration between forensic experts and biometric technology specialists include collaborative studying the frequency and identification significance of external human characteristics, as well as individual features of movements and actions, determined by habits and skills and used for forensic identification. They share common goals such as investigating the causes of erroneous identifications, exploring the ways to illegally bypass biometric security systems, and developing methods to counter criminal attacks.